Intraoperative high-resolution ultrasound and contrast-enhanced ultrasound of peripheral nerve tumors and tumorlike lesions - Pedro, Maria Teresa; Antoniadis, Gregor; Scheuerle, Angelika; Pham, Mirko; Wirtz, Christian Rainer; Koenig, Ralph W. (Neurosurgical focus, 2015)
The diagnostic workup and surgical therapy for peripheral nerve tumors and tumorlike lesions are challenging. Magnetic resonance imaging is the standard diagnostic tool in the preoperative workup. However, even with advanced pulse sequences such as diffusion tensor imaging for MR neurography, the ability to differentiate tumor entities based on histological features remains limited. In particular, rare tumor entities different from schwannomas and neurofibromas are difficult to anticipate before surgical exploration and histological confirmation. High-resolution ultrasound (HRU) has become another important tool in the preoperative evaluation of peripheral nerves. Ongoing software and technical developments with transducers of up to 17-18 MHz enable high spatial resolution with tissue-differentiating properties. Unfortunately, high-frequency ultrasound provides low tissue penetration. The authors developed a setting in which intraoperative HRU was used and in which the direct sterile contact between the ultrasound transducer and the surgically exposed nerve pathology was enabled to increase structural resolution and contrast. In a case-guided fashion, the authors report the sonographic characteristics of rare tumor entities shown by intraoperative HRU and contrast-enhanced ultrasound.
Gesehen am 01.07.2020